Subjectivity, Agency and Political Pedagogy in the Primary School. Issue 1 (March 2014) - Teague, Laura
This article explores power, resistance and agency in relation to pedagogic politics aiming to disrupt schooling inequalities. It theorises the concept of agency in enacting politics in the classroom and attempts to demonstrate the precariousness of the position of the teaching subject engaging in radical politics. Focusing on a detailed data excerpt depicting resistance towards classroom testing regimes, the article explores the way in which the agency to resist this practice (as momentary as it may be) is developed collectively by the students and the teacher. Yet it also argues that the teacher can never risk relinquishing authority altogether and that this shoring up of normative power relations in the classroom occurs simultaneously with more radical moves to resist such practices. Thus the article engages more broadly with the complexity and ambivalence of engaging with radical politics in the classroom, arguing that political enactments aimed at disrupting educational inequalities are often fraught with contradictions and undercut by the need remain recognisable enough (as a proper teacher or student).